Cortical and Striatal Reward Processing in Parkinson’s Disease Psychosis - Garofalo, Sara; Justicia, Azucena; Arrondo, Gonzalo; Ermakova, Anna O.; Ramachandra, Pranathi; Tudor-Sfetea, Carina; Robbins, Trevor W.; Barker, Roger A.; Fletcher, Paul C.; Murray, Graham K. (Frontiers in Neurology, 2017)
Psychotic symptoms frequently occur in Parkinson’s disease, but their pathophysiology is poorly understood. According to the National Institute of Health RDoc programme, the pathophysiological basis of neuropsychiatric symptoms may be better understood in terms of dysfunction of underlying domains of neurocognition in a transdiagnostic fashion. Abnormal cortico-striatal reward processing has been proposed as a key domain contributing to the pathogenesis of psychotic symptoms in schizophrenia. This theory has received empirical support in the study of schizophrenia spectrum disorders and preclinical models of psychosis, but has not been tested in the psychosis associated Parkinson’s disease. We therefore investigated brain responses associated with reward expectation and prediction error signalling during reinforcement learning in Parkinson’s disease associated psychosis. An instrumental learning task with monetary gains and losses was conducted during an fMRI study in patients with Parkinson’s disease with (n=12), or without (n=17), a history of psychotic symptoms, along with a sample of healthy controls (n=24). We conducted region of interest analyses in the ventral striatum, ventromedial prefrontal and posterior cingulate cortices, and whole-brain analyses. There was reduced activation in Parkinson’s disease patients with a history of psychosis compared to those without in the posterior cingulate cortex and the ventral striatum during reward anticipation (p<0.05 small volume corrected). The results suggest that cortical and striatal abnormalities in reward processing, a putative pathophysiological mechanism of psychosis in schizophrenia, may also contribute to the pathogenesis of psychotic symptoms in Parkinson’s disease. The finding of posterior cingulate dysfunction is in keeping with prior results highlighting cortical dysfunction in the pathogenesis of Parkinson’s disease psychosis.